Measurement of family economic status - Yadollahi, Mehdi; Paim, Laily (Marsland Press, 2010)
The concept of family economic has become important around the world. It has been realized that communities based family economic can play a fundamental role in poverty alleviation. Measuring of family economic status is an important step in developing family economic strategies to achieve poverty reduction. This paper used qualitative approaches to illustrated family economic status. The purpose of this study is to explore the concept and indictors of family economic. The literature derived from my study in family economic management.